PERAN PENYULUH AGAMA ISLAM DALAM MENINGKATKAN KERUKUNAN ANTAR UMAT BERAGAMA (STUDI DESKRIPTIF SOSIOLOGIS DI KANTOR URUSAN AGAMA KECAMATAN JUNREJO KOTA BATU) - Salma Lailatussiam; Ibnu Jazari; Humaidi Humaidi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2021)
Religious harmony is living in peace and mutual tolerance for all despite different religions. The religion adopted by the Junrejo community is very diverse, ranging from Islam, Christianity, Hinduism, Catholicism and Buddhism. So conflicts with religious backgrounds can occur anytime and anywhere. Therefore, the role of Islamic religious instructors is very much needed for the creation of a society that respects each other even though they have different beliefs. This research was conducted at the Office of Religious Affairs, Junrejo District to determine the objective conditions, the role of Islamic religious educators, and the obstacles experienced in increasing inter-religious harmony. This study uses a descriptive qualitative method, using three collection techniques, namely observation, interview and documentation. The results of this study show that the objective conditions of inter-religious harmony are still very conducive. The role of the Islamic Religious Counselor is to provide broad religious insight to all people in order to strengthen the friendship. The obstacle is because of the limited time in the midst of a busy community and also because the number of target groups is not proportional to the number of religious instructors in Junrejo District, Batu City.Keywords : Islamic religious educator, Harmony, Religious people